The Influence of Psychological Empowerment and Knowledge Management Readiness on Organizational Business Performance Mediated by Micro-Innovation - Ekosaputro, Adriansyah; Abdurrahman Sadikin (Open Access Indonesia Journal of Social Sciences, 2024)
In the dynamic landscape of modern business, organizations are increasingly recognizing the pivotal role of human capital in driving sustainable growth and competitive advantage. This study delves into the intricate relationship between psychological empowerment, knowledge management readiness, and their combined impact on organizational business performance. It further examines the mediating role of micro-innovation in this relationship, shedding light on how these factors interact to foster innovation and enhance overall performance. A quantitative research methodology was employed, involving a survey of 250 employees across diverse industries. Structural equation modeling (SEM) was utilized to analyze the data and test the hypothesized relationships between the variables. The findings of this study reveal a significant positive relationship between psychological empowerment and knowledge management readiness. Both psychological empowerment and knowledge management readiness were found to have a direct positive impact on organizational business performance. Moreover, micro-innovation was identified as a significant mediator in this relationship, indicating that it plays a crucial role in channeling the effects of psychological empowerment and knowledge management readiness towards improved business performance. This research underscores the importance of fostering a psychologically empowering work environment and cultivating knowledge management readiness within organizations. By nurturing these factors, organizations can stimulate micro-innovation, which in turn drives organizational business performance. The implications of these findings for managers and practitioners are discussed, along with recommendations for future research directions.